Hemodynamic assessment of partial mechanical circulatory support: data derived from computed tomography angiographic images and computational fluid dynamics - Karmonik, Christof; Rengier, Fabian; Meredig, Hagen; Farag, Mina; Müller-Eschner, Matthias; Arif, Rawa; Kauczor, Hans-Ulrich; Karck, Matthias; Ruhparwar, Arjang (Cardiovascular Diagnosis and Therapy, 2015)
Partial mechanical circulatory support represents a new concept for the treatment of advanced heart failure. The Circulite Synergy Micro Pump®, where the inflow cannula is connected to the left atrium and the outflow cannula to the right subclavian artery, was one of the first devices to introduce this concept to the clinic. Using computational fluid dynamics (CFD) simulations, hemodynamics in the aortic tree was visualized and quantified from computed tomography angiographic (CTA) images in two patients. A realistic computational model was created by integrating flow information from the native heart and from the Circulite device. Diastolic flow augmentation in the descending aorta but competing/antagonizing flow patterns in the proximal innominate artery was observed. Velocity time curves in the ascending aorta correlated well with those in the left common carotid, the left subclavian and the descending aorta but poorly with the one in the innominate. Our results demonstrate that CFD may be useful in providing a better understanding of the main flow patterns in mechanical circulatory support devices.
Gesehen am 16.06.2020